Legal Protection for Victims of Cybercrime as a Form of Transnational Crime - Zamroni, Zamroni; Basri, Basri (Jurnal Ius Constituendum, 2024)
The study aims to analyze the legal protection of legal protection for victims of cyber crime as a form of transnational crime. In addition to creating laws and regulations that safeguard victims of phishing, the goal of this research is to establish legal protection for victims of cybercrime, a form of transnational crime. This study employs a normative juridical research methodology that blends statutory and conceptual frameworks. The following are the results of the research: 1) Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions and Law Number 27 of 2022 concerning Personal Data Protection are examples of previous legislative regulations that regulate protections for victims of cross-border information crimes and electronic transactions. 2) Cybercrime victims' legal protection as a form of transnational crime. Essentially, two methods are available for use: 1) the procedural rights model, in which the victim has the right to attend all court proceedings and takes a more active role in the prosecution; 2) the service model, according to which victims are seen as individuals who require assistance from law enforcement in order to feel as though their rights are upheld in a just setting. Every step of the investigation, trial, and post-trial phases of the process needs to include virtual and in-person support for victims of cybercrime.